EVALUASI KELAYAKAN PEMEKARAN KABUPATEN LUWU TENGAH MENJADI DAERAH OTONOM BARU DI KABUPATEN LUWU PROVINSI SELAWESI SELATAN - TANGKE, RAWINDA; TAMPI, GUSTAAF; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2021)
This study aims to describe and analyze the dynamics of processes and factors that hinder the formation of Central Luwu Regency. Research design is a qualitative based research method that aims to describe the findings in the field. The data collected by field officers include the dynamics of community leaders and obstacles in the process of regional expansion. Descriptive analysis is used to analyze the dynamics of processes and factors that hinder the formation of Central Luwu Regency. The result of the study is the dynamics of the process on conflicts of interest between the pros and cons of walenrang-lamasi censure should join in Palopo City, because facilities and infrastructure, economy, and community service facilities can not be ascertained to meet the results of the provincial government study. Keywords: Evaluation; Feasibility; Expansion; Autonomous Region